De l'emphytéose au louage ordinaire par la voie mal éclairée du doute - Frenette, François (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
Restrictions upon the emphyteutic holder's rights that are contrary to article 569 C.c. are sufficient justification for depriving a transaction of its emphyteutic character. However it is erroneous, upon rendering such a decision, to pretend that emphyteusis carries with it alienation of property and that a contract so qualified by parties must be considered as an ordinary lease if any doubts arise as to the real nature of the agreement.